Pengaruh Gaya Kepemimpinan dan Beban Kerja terhadap Produktivitas Kerja Karyawan Direktorat Keuangan dan Manajemen Risiko PT Pelindo Multi Terminal - Josefa Sitorus; Jamardua Haro; Suri Purnami; Harris P Nasution; Ratna Dewi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the effect of leadership style and workload on employee productivity in the Finance and Risk Management Directorate of PT Pelindo Multi Terminal. The research was conducted from February to July 2025 with 31 employee respondents. The study employed a quantitative approach, collecting data through questionnaires and analyzing it using multiple linear regression. The research sought to understand how leadership style and workload influence the productivity of employees within this specific department. The results indicate that, partially, leadership style and workload have no significant effect on employee productivity, with significance values greater than 0.05. This suggests that individual leadership styles and workloads, when considered separately, may not have a strong direct impact on productivity. However, when analyzed simultaneously, both variables significantly influence employee productivity, with a significance value of less than 0.05. The coefficient of determination reveals that leadership style and workload contribute 16.3% to employee productivity, indicating that while these factors play a role, the majority of the variation in productivity (83.7%) is due to other factors not explored in this study. These findings highlight the need for the company to consider a holistic approach to human resource management, focusing not only on leadership style and workload but also on other variables that could further enhance employee productivity. This research provides valuable input for improving organizational strategies